SEDs and Beaming Effect for Fermi Blazars - Jun-Hui Fan (Journal of Astronomy and Space Sciences, 2016)
In this work, based on our previous calculations of spectral energy distributions for a sample of Fermi blazars (Fan et al. 2015a), we calculated the radio loudness and performed correlation analyses. Our analysis results show that radio loudness is closely anti-correlated with synchrotron peak frequency and positively correlated with gamma-ray luminosity, suggesting that the gamma-ray emissions are strongly beamed.